2020
DOI: 10.15406/mojap.2020.07.00309
|View full text |Cite
|
Sign up to set email alerts
|

Biometric analysis of the area of the foramen magnum using the ImageJ software, and its correlation with the Radinsky and Teixeira formulas

Abstract: Introduction: The knowledge of biometrics in the area of the foramen magnum is of importance in the pathophysiology of several disorders of the craniocervical junction, as well as for anthropology, anatomy and forensic medicine. The analysis of the area using image technology is still very scarce in the literature. Objective: Determine the area of the foramen magnum using ImageJ and correlate it with the areas calculated by the formulas of Radinsky and Teixeira. Methodology: 104 human dry skulls of adults we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…22 Differences are observed when calculating the area of the foramen magnum by Radinsky's method, Teixeira's method, and while using computer software. 22,23 Similar to the previous studies, the present study also found that the mean values of various metric measurements were greater in males than in females. Sexual dimorphism could be established from the foramen magnum which was 71% by multivariate analysis and 70.5% for selected variables who showed higher classification accuracy in step wise method in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…22 Differences are observed when calculating the area of the foramen magnum by Radinsky's method, Teixeira's method, and while using computer software. 22,23 Similar to the previous studies, the present study also found that the mean values of various metric measurements were greater in males than in females. Sexual dimorphism could be established from the foramen magnum which was 71% by multivariate analysis and 70.5% for selected variables who showed higher classification accuracy in step wise method in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The shape of the foramen magnum is not always round and there are various shapes like oval, tetragonal, pentagonal, hexagonal, egg, and irregular 22 . Differences are observed when calculating the area of the foramen magnum by Radinsky's method, Teixeira's method, and while using computer software 22,23 …”
Section: Discussionmentioning
confidence: 99%